Grand Trunk Pacific steamer PRINCE GEORGE at the company dock in Seattle, approximately 1912 (1912)
PH Coll 794.78 Canada's Grand Trunk Pacific Railway, having established its western terminus at Prince Rupert, brought to the Northwest in 1910 two handsome passenger steamships, PRINCE RUPERT and PRINCE GEORGE, for coastal feeder service to Prince Rupert via Vancouver, Victoria, and Seattle. The vessels were 320 feet long, beam was 42.75 feet, moulded depth from shelter deck was 26 feet, gross tonnage was 3,380. The four-cylinder triple-expansion steam engines developed 6,000 horsepower, yielding a cruise speed of 16 knots and a trial speed over 18 knots. She went on to serve Alaskan routes for much of her career before being destroyed by fire in Ketchikan in 1945. (Source: Newell, Gordon, ed. "The H.W. McCurdy Marine History of the Pacific Northwest." Seattle: The Superior Company, 1966.) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number